Notes on Bonea Roewer, 1914 and Lomanius Roewer, 1923 (Opiliones: Laniatores: Podoctidae), with the description of three new species from China - Zhang, Chao; Kury, Adriano B.; Zhang, Feng (Zootaxa, 2013)
The harvestman genus Bonea Roewer, 1914 and its type species B. sarasinorum Roewer, 1914 are redescribed based on the type material. In addition, two new species of Bonea from Hainan Island, China, are described and illustrated: B. zhui sp. nov. and B. tridigitata sp. nov. A new species of Lomanius Roewer, 1923 from Yunnan Province, China, is also described and illustrated: L. bulbosus sp. nov.. Keys to the 10 species of Bonea and the six species of Lomanius are provided. Paralomanius Goodnight & Goodnight, 1948 is revalidated from the synonymy of Lomanius, carrying as junior synonym Eulomanius Roewer, 1949, and containing two species from Micronesia (Paralomanius longipalpus Goodnight & Goodnight, 1948) and Philippines (Paralomanius mindanaoensis (Suzuki, 1977) new status). Bonea is transferred from the Ibaloniinae to Podoctinae. These are the first records of named species of Podoctidae from China.